In the Footsteps of an Observer – Looking at Edvard Munch in Åsgårdstrand - Mathiesen, Ilmi Gutzeit (Nordic Journal of Art & Research, 2021)
This article presents an arts based approach to some of the motifs that Edvard Munch painted during his many stays in the Norwegian town of Åsgårdstrand. The author examines the relationship between Munch’s and her own observations made from the very same vantage points in the landscapes. The theoretical thrust of the article is informed by arts based research as promoted by art education theorists Barone and Eisner (2012) and art therapy researcher McNiff (2013). It is also inspired by Pink’s text “Doing sensory ethnography” (2009), which highlights the multisensory experience and recognises the significance of the researcher’s own presence in the data collection process. A key tool in the research project was a tablet device (iPad), used both as a camera in the field and as a tool for creative artistic exploration in practice. The method involved digitally painting Munch’s figures onto photos taken from the same places as the artist must have stood when inspired to paint his famous pictures. The author argues that a tablet with artistic software applications can serve as a versatile and handy “portable studio”, facilitating immediate first-hand experience and understanding. The concluding discussion focuses on how this practical arts based approach to the work of a famous artist can be implemented in an art education setting.